Dual‐band and dual‐polarized antenna with endfire radiation. Issue 13 (13th September 2017) - Ding, Kang; Gao, Cheng; Wu, Yanjie; Qu, Dexin; Zhang, Bing; Wang, Yumeng
Abstract : A novel dual‐band endfire antenna with dual polarisation is proposed. The antenna is composed of a shorted metal cavity which functions as a magnetic dipole, a bowtie‐shaped electric dipole and an I‐shaped resonator (ISR) array. Owing to the combination of complementary dipoles, circularly polarised (CP) electromagnetic waves are generated in the endfire direction at the lower band. A quasi‐Yagi antenna structure is adopted to attain broadband linearly polarised (LP) radiation in the upper band. In addition, an ISR structure is loaded to improve the gain in endfire direction. The measured 10‐dB impedance bandwidths are 3.93% at the lower band and 29.45% at the upper band, respectively, and the 3‐dB axial‐ratio bandwidth of 150 MHz (5.76 to 5.91 GHz) is observed in the CP band. Besides, the ISR loaded antenna demonstrates 2–3.5 dB gain improvement over the operational band. This antenna could find applications in radio‐frequency identification and indoor positioning systems.